Analysing The Impact of Halal Certification for the Development of Micro, Small, and Medium Enterprises' Competitiveness in Besuki Raya, Indonesia - Moehammad Fathorrazi; Agus Mahardiyanto; Lusiana Ulfa Hardinawati; Zainuri; Suparman; Akhmad Munir; Agus Priyono; Moh Shaleh (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This research attempts to analyze the impacts experienced by Micro, Small, and Medium Enterprises' (MSMEs) Competitiveness after obtaining Halal certification. The study focused on MSMEs in the Food and Beverage sector using a qualitative exploratory approach. This research was conducted using a qualitative descriptive approach and using a purposive sampling method. One respondent was selected from each district to ensure that all districts within the study area were represented. The rationale for this approach was to secure minimal but sufficient representation from every district under investigation. The analysis results show that halal certification contributes not only to business growth but also to the advancement of Islamic economic values by embedding halalan tayyiban principles into the supply chain, promoting transparency, and reinforcing consumer rights in predominantly Muslim markets. The study further highlights that Halal certification contributes to advancing of Islamic economic values by embedding the principles of halalan tayyiban into production and distribution processes, promoting business transparency, and reinforcing consumer rights in predominantly Muslim communities. Therefore, Halal certification serves not only as a religious or legal obligation but also as a strategic instrument for sustainable growth and empowerment of MSMEs in regional economic development.